Features of legal protection of medical inventions: present and future - V. I. Teremetskyi; A. V. Matviichuk; O. M. Muzychuk; M. H. Shcherbakovskyi; O. V. Oderii (Patologìâ)
The modern legal doctrine of intellectual property practically does not investigate the terms of legal protection of inventions in medical practice.